Hubungan antara Pendidikan orang tua, Dukungan orang tua dengan perilaku anak menggosok gigi di SD 2 Ba,a - Tesa Lonika Naomi Messakh; Enna Rossalina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Parental support is part of the learning family of a child's behavior which includes informational, emotional, instrumental, and assessment support. So that support will affect the behavior of children, one of which is brushing teeth. The purpose of the study was to analyze the relationship between parental support, education and the behavior of children brushing their teeth at SD 2 Ba,a. This study used a quantitative method with a cross sectional analytical design, the samples used were parents and students in grades 1-4 aged 6-10 years with a total of 120 using total sampling. The results showed that the majority of parental support was moderate support as many as 88 respondents (73.3%), the behavior of children brushing their teeth was not good as many as 91 students (75.8%) and education namely secondary education as many as 60 people (50%). Bivariate analysis using Kendals tau b showed that there was a significant relationship between parental support and the behavior of children brushing their teeth at SD 2 Ba,a with sig. (2-tailed) 0.000 (<0.01) which means Ha1 is accepted and the correlation coefficient value is 0.372*, and there is a significant relationship between parental education and child's behavior in brushing teeth with sig. (2-tailed) 0.000 (<0.01) which means Ha2 is accepted and the value of the correlation coefficient between is 0.559* Parents or guardians are expected to provide good support so that it can influence the behavior of children brushing teeth better to maintain health teeth and mouth.